2021
DOI: 10.21203/rs.3.rs-566869/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Medicinal plants in Butalejja District, Eastern Uganda: plants, medical importance, conservation and Medicinal Traditional Knowledge

Abstract: Background: Currently, the global consumption of herbal medicine is increasing steadily, incurring extinction risks to the medicinal plant species. Uganda is one of the top ten countries with alarming levels of loss of medicinal plant biodiversity, and erosion of the associated Medicinal Traditional Knowledge (MTK). This study documented medicinal plant species, and examined the approaches used in preventing extinction of these species and the associated MTK in Butalejja district. Methods: A cross – sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
1
Order By: Relevance
“…The number of medicinal plant species reported in the current study is generally small compared to previous ethnobotanical and/or ethnopharmacological surveys conducted in Uganda [48,[50][51][52][53][54][55]. The earlier studies were mostly based in rural settings, and focused on documenting HM used for treating all the health complications prevalent in the study communities; this resulted in higher numbers of species reported by those studies, as compared to the current study.…”
Section: Herbal Medicine Diversity Methods Of Preparation and Adminis...contrasting
confidence: 56%
“…The number of medicinal plant species reported in the current study is generally small compared to previous ethnobotanical and/or ethnopharmacological surveys conducted in Uganda [48,[50][51][52][53][54][55]. The earlier studies were mostly based in rural settings, and focused on documenting HM used for treating all the health complications prevalent in the study communities; this resulted in higher numbers of species reported by those studies, as compared to the current study.…”
Section: Herbal Medicine Diversity Methods Of Preparation and Adminis...contrasting
confidence: 56%